Immobilization of β-Galactosidase by Encapsulation of Enzyme-Conjugated Polymer Nanoparticles Inside Hydrogel Microparticles - Suvarli, Narmin; Wenger, Lukas; Serra, Christophe; Perner-Nochta, Iris; Hubbuch, Jürgen; Wörner, Michael (Frontiers in Bioengineering and Biotechnology, 2022)
Increasing the shelf life of enzymes and making them reusable is a prominent topic in biotechnology. The encapsulation inside hydrogel microparticles (HMPs) can enhance the enzyme’s stability by preserving the native conformation and facilitating continuous biocatalytic processes and enzyme recovery. In this study, we present a method to immobilize β-galactosidase by, first, conjugating the enzyme onto the surface of polymer nanoparticles and then encapsulating these enzyme-conjugated nanoparticles (ENPs) inside HMPs using microfluidic device paired with UV-LEDs. Polymer nanoparticles act as anchors for enzyme molecules, potentially preventing their leaching through the hydrogel network especially during swelling. The affinity binding (through streptavidin-biotin interaction) was used as an immobilization process of enzyme on the surface of polymer nanoparticles. The hydrogel microparticles of roughly 400 µm in size (swollen state) containing unbound enzyme and ENPs were produced. The effects of encapsulation and storage in different conditions were evaluated. It was discovered that the encapsulation in acrylamide (AcAm) microparticles caused an almost complete loss of enzymatic activity. Encapsulation in poly(ethylene glycol)-diacrylate microparticles, on the other hand, showed a residual activity of 15-25 %, presumably due to a protective effect of PEG during polymerization. One of the major factors that affected the enzyme activity was presence of photoinitiator exposed to UV-irradiation. Storage studies were carried out at room temperature, in the fridge and in the freezer throughout 1, 7 and 28 days. The polymer nanoparticles showcased excellent immobilization properties and preserved the activity of the conjugated enzyme at room temperature (115 % residual activity after 28 days), while a slight decrease was observed for the unbound enzyme (94 % after 28 days). Similar trends were observed for encapsulated ENPs and unbound enzyme. Nevertheless, storage at -26 °C resulted in an almost complete loss of enzymatic activity for all samples.